2016
DOI: 10.1136/bmjopen-2015-010417
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine used in childbirth and for childhood diarrhoea in Nigeria's Cross River State: interviews with traditional practitioners and a statewide cross-sectional study

Abstract: ObjectivesExamine factors associated with use of traditional medicine during childbirth and in management of childhood diarrhoea.DesignCross-sectional cluster survey, household interviews in a stratified last stage random sample of 90 census enumeration areas; unstructured interviews with traditional doctors.SettingOil-rich Cross River State in south-eastern Nigeria has 3.5 million residents, most of whom depend on a subsistence agriculture economy.Participants8089 women aged 15–49 years in 7685 households rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
4
17
0
2
Order By: Relevance
“…Our analysis found that lower educational level was significantly correlated with increased traditional and complementary medicine use for maternal health and wellbeing. Similar to this finding, other studies have also reported that African women who use traditional medicine were more likely to be less educated [45,46]. Increased use of traditional medicine among the less educated group in this study could be partly explained by the fact that lower education may limit African women's knowledge about available healthcare options in Australia.…”
Section: Discussionsupporting
confidence: 87%
“…Our analysis found that lower educational level was significantly correlated with increased traditional and complementary medicine use for maternal health and wellbeing. Similar to this finding, other studies have also reported that African women who use traditional medicine were more likely to be less educated [45,46]. Increased use of traditional medicine among the less educated group in this study could be partly explained by the fact that lower education may limit African women's knowledge about available healthcare options in Australia.…”
Section: Discussionsupporting
confidence: 87%
“…Eighteen studies reported the prevalence rates of TCAM use during pregnancy, 24 82-95 childbirth [94][95][96] and for pregnancy termination. 97 Between 12% and 90.3% (mean, 48.4%) of pregnant women were reported to use a TCAM product during pregnancy, a rate consistent across studies drawn from large sample sizes 84 85 93-95 (25.5%-67.5% (average, 45.3%)) and from small sample sizes 24 83 86-92 (12%-90.3% (average, 50.1%)).…”
Section: Prevalence Of Tcam Use In Health Subpopulations Pregnancy Cmentioning
confidence: 99%
“…(Shenton, 2004): we have adopted a method clearly defined in a protocol with predefined rules for decision making. This methodology has been successfully applied in other studies (Hovey et al, 2017;Sarmiento, Zuluaga, & Andersson, 2016). Traditional midwives are committed to the process of intercultural dialogue and open to share their knowledge.…”
Section: Quality Assurance: Trustworthinessmentioning
confidence: 99%